We have to verify the value of lim x--> 1[ (x^2 - 6x + 5)/(x - 1)]

Substituting x = 1 we get the indeterminate form 0/0.

So, we can use l'Hopital's rule and substitute the numerator and denominator by their derivatives.

=> lim x--> 1[ (2x - 6)/1]

Substitute x = 1

=> 2 - 6

=> -4

**The value of lim x--> 1[ (x^2 - 6x + 5)/(x - 1)] is not 4
but -4.**

## See eNotes Ad-Free

Start your **48-hour free trial** to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Already a member? Log in here.